Psychological Impact of Sexual Violence and Government Efforts in Making Recovery (Universitas Negeri Semarang, 2021)
This article aims to describe the psychological impact of sexual violence and the government's efforts to restore victims. The discussion of this article uses a written study from various reading sources which is entirely aimed at developing speculations related to the growth of victims, the causes of sexual brutality in children and the impact and treatment of sexual crimes on children, as well as on adults. Sexual violence is an activity that is carried out by someone without the consent or willingness of the person who is the victim of the sexual violence. In this sexual violence the acts are in the form of rape by a stranger, rape in a marriage relationship and there is also courtship, this sexual harassment can be in the form of mental or physical abuse, forced abortion, and there is also sexual abuse of children. Of the types of sexual violence is a form of violation of human rights (HAM) that can have a psychological impact on victims of sexual violence.